2017
DOI: 10.1002/ehs2.1255
|View full text |Cite
|
Sign up to set email alerts
|

Does the ecological concept of disturbance have utility in urban social–ecological–technological systems?

Abstract: The ecological concept of disturbance has scarcely been applied in urban systems except in the erroneous but commonplace assumption that urbanization itself is a disturbance and cities are therefore perennially disturbed systems. We evaluate the usefulness of the concept in urban ecology by exploring how a recent conceptual framework for disturbance (Peters et al. 2011, Ecosphere, 2, art 81) applies to these social-ecological-technological systems (SETS). Case studies, especially from the Long-Term Ecological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 96 publications
4
86
0
Order By: Relevance
“…A recovery period of approximately two weeks is similar to recovery times found for algal biomass and stream metabolism in naturally flashy desert streams (Fisher et al 1982, Grimm 1987. The similarities between urban and desert streams in response to a major disturbance, in spite of drastically different abiotic conditions, confirm the idea that hydrological disturbances are a fundamental driver of ecosystem functioning across a range of stream types (Poff et al 1997) and point to the need for a better understanding of disturbance ecology within urban ecosystems (Grimm et al 2017).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A recovery period of approximately two weeks is similar to recovery times found for algal biomass and stream metabolism in naturally flashy desert streams (Fisher et al 1982, Grimm 1987. The similarities between urban and desert streams in response to a major disturbance, in spite of drastically different abiotic conditions, confirm the idea that hydrological disturbances are a fundamental driver of ecosystem functioning across a range of stream types (Poff et al 1997) and point to the need for a better understanding of disturbance ecology within urban ecosystems (Grimm et al 2017).…”
Section: Discussionsupporting
confidence: 62%
“…, Grimm ), suggesting that urban streams can adapt to floods and other disturbances in spite of myriad environmental stressors (Grimm et al. ). Overall, we found that urban streams can exhibit high metabolic activity despite a multitude of physicochemical stressors and that this metabolism rapidly recovers from floods, regardless of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, existing conditions prior to the extreme events were instrumental to the character and extent of post‐event actions. This is consistent with views from ecological theory that suggest system state is a primary factor in impacts of extreme events (disturbances) (Grimm, Pickett, Hale, & Cadenasso, ; Peters et al, ). Further analysis will be needed to understand the factors that enabled post‐event advances, compared to other situations where institutional inertia or other social factors stalled progress toward low‐carbon energy systems.…”
Section: Discussionsupporting
confidence: 89%
“…Stokols () also emphasizes the importance of interconnections, as in this paper, though the bounding of those elements may differ. Other existing literature on SETS primarily focus on definitions and conceptual framing (Grabowski et al, ; Grimm et al, ; Hale et al, ; Krumme, ; McPhearson et al, ; Ramaswami et al, ) or discuss the three components independently. Similar to analysis by Tellman et al (), we expand on existing SETS literature by directly applying the SETS lens to infrastructure development and management, particularly in relation to identifying maladaptive lock‐in processes and establishing approaches to help infrastructure adapt to the effects of extreme events.…”
Section: Sets Characteristics and Challenges For Infrastructure Systemsmentioning
confidence: 99%